Whole‐body reversible neuropathic pain associated with right parieto‐temporal operculum single inflammatory lesion in a patient with multiple sclerosis: A case report. (22nd August 2019) - Poncet‐Megemont, Louis; Dallel, Radhouane; Chassain, Carine; Perrey, Antoine; Mathais, Sophie; Clavelou, Pierre; Moisset, Xavier
Abstract: Background: The posterior insula and the medial parietal operculum (PIMO) are part of the pain network. Pain can be induced by direct stimulation of the PIMO, but the clinical consequence of lesions in this brain area is not well known. Case report: We report the case of a patient with multiple sclerosis who presented a relapse characterized by isolated widespread neuropathic pain. The MRI displayed a single new inflammatory lesion in the juxta cortical white matter of the opercular region. This lesion was extended to the parietal operculum and was associated with the pain syndrome. The patient was treated with high‐dose intravenous methylprednisolone, and the pain disappeared progressively. Diffusion‐tensor MRI showed that some of the fibres passing through the lesion ended in the PIMO. Conclusion: Based on diffusion‐tensor MRI we hypothesize that the partial disconnection from afference to the PIMO can lead to widespread neuropathic pain. Significance: Most of the data concerning the functional role of the PIMO come from stereoelectroencephalography in presurgical evaluation of epilepsy, or from functional imaging (PET or fMRI). There is, however, very few data on the consequences of the lesion of the PIMO. Here, we report the first case of a transient widespread pain syndrome associated to a single, small and reversible inflammatory lesion of the PIMO. Thus, this case highlights the key role of the PIMO in spatial perception of pain.